Clinical and instrumental characteristics of axial involvement in psoriatic arthritis in real-life clinical practice - E. E. Gubar; T. V. Korotaeva; Yu. L. Korsakova; E. Yu. Loginova; A. V. Smirnov; A. V. Sukhinina; M. M. Urumova; S. I. Glukhova (Научно-практическая ревматология)
Objective: to evaluate clinical and instrumental characteristics of axial lesion in psoriatic arthritis (PsA) in real-life clinical practice.Subjects and methods. Examination were made in 52 patients (32 men and 20 women) with back pain recorded either at the time of their admission or in their medical histories. The inflammatory back pain (IBP) was diagnosed according to the Assessment of SpondyloArthritis international Society (ASAS) criteria. Back pain lasting over three months without meeting the ASAS criteria was taken to be chronic back (chrBP). Hands, feet, pelvis, cervical spine (CSP) and lumbar spine (LSP) were X-rayed. Erosions, osteolysis, and periarticular osteo-proliferative lesions were evaluated applying PsA-modified Sharp/van der Heijde score (SHS). Sacroiliitis (SI) was considered radiologically significant (r-sSI) when it was bilateral grade II or higher, or unilateral grade III or higher by Kellgren. 15 patients without r-sSI had their sacroiliac joints (SIJs) scanned using magnetic resonance imaging (MRI). Syndesmophytes, paravertebral ossifications, constriction and ankylosis of the CSP zygapophysial joints were considered to be radiological signs of psoriatic spondylitis. HLA-B27 typing was performed in 45 patients.Results and discussion. IBP was identified in 34 (66.7%), chrBP in 17 (33.3%) patients; 15 patients (28.8%) were of advanced age (over 40) at the onset of IBP/chrBP; 30 cases (57.7%) had r-sSI; in 18 cases SI was not detected. 13 out of 30 r-sSI patients (43.3%) didn’t suffer IBP. Erosions were detected in 38 (76%) patients, osteolysis in 13 (26%) and osteo-proliferative lesions in 18 (36%) patients. Average SHS was 82.79±64.77 correlating with the presence of r-sSI (r=0,46; p<0,05). Correlation of r=0.35 was found between r-sSI and the spine limited mobility according to Bath Ankylosing Spondylitis Metrology Index (BASMI); r-sSI was detected with much higher statistical significance in the presence of periarticular osteo-proliferative lesions than in the absence of such (р=0.02). In PsA patients having periarticular osteolysis, axial lesion in the form of asymmetric syndesmophytes was detected ten times more frequently than in those not having it (OR=10; 95% CI: 1.63–61.327). In CSP, syndesmophytes developed two times more frequently than in LSP (p=0.01). Discrete CSP lesions in the absence of any LSP changes was observed in 30% of cases. SI was MRI detected in 2 (13.3%) patients. In 9 (18.0%) patients axial lesions were observed without SI. 15 patients (33.3%) were HLA-B27 positive. A set of specific PsA axial skeletal involvement features were revealed: possibility of oligosymptomatic clinical presentation; patient’s advanced age at the back pain onset; association with severe destructive peripheral arthritis; and more pronounced CSP lesions as compared to LSP. An alternative phenotype patient group (18%) without X-ray or MRI SI but with spine involvement was identified. Key words: psoriatic arthritis; axial lesion>˂ 0,05). Correlation of r=0.35 was found between r-sSI and the spine limited mobility according to Bath Ankylosing Spondylitis Metrology Index (BASMI); r-sSI was detected with much higher statistical significance in the presence of periarticular osteo-proliferative lesions than in the absence of such (р=0.02). In PsA patients having periarticular osteolysis, axial lesion in the form of asymmetric syndesmophytes was detected ten times more frequently than in those not having it (OR=10; 95% CI: 1.63–61.327). In CSP, syndesmophytes developed two times more frequently than in LSP (p=0.01). Discrete CSP lesions in the absence of any LSP changes was observed in 30% of cases. SI was MRI detected in 2 (13.3%) patients. In 9 (18.0%) patients axial lesions were observed without SI. 15 patients (33.3%) were HLA-B27 positive. A set of specific PsA axial skeletal involvement features were revealed: possibility of oligosymptomatic clinical presentation; patient’s advanced age at the back pain onset; association with severe destructive peripheral arthritis; and more pronounced CSP lesions as compared to LSP. An alternative phenotype patient group (18%) without X-ray or MRI SI but with spine involvement was identified.